The Scientific Of Quranic Respond To Phenomenon Of Global Warming Issues - Kamal, Muhamad Ali Mustofa (Qaf: Jurnal Ilmu Al-Qur'an dan Tafsir, 2016)
The problem of global warming is regarded as one of the most serious environmental problems of our time, concerning which experts have held many conferences and published many articles about its dire consequences. al-Qur’ân was object of interpretation and was sources of law and inspiration to context with reality in the nature. In this context, What is the scientiﬁ c of Qur’anic respond to solve the global warming disaster. This riset used qualitatife method with methodology of Qur’âniah analysis was also used to explain the meaning of verses and Syahrûr hermeneutic also. Global Warming disaster is sunnatullâh and also caused by human hands as catalyzer. The negative effects of Global Warming can be resolved by changing the attitudes and actions of mankind for an environmentally safe world. Allâh has created everything in this universe in due proportion and measure both quantitatively and qualitatively. These changes include developing and harnessing new forms of energy that was environmentally safe, the prevention of deforestation and implementation of increasing ﬂ ora environments, and ultimately inﬂ uence and educate the public about environmental issues